2017
DOI: 10.1080/02713683.2017.1368085
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Combined Caffeic Acid Phenethyl Ester and Bevacizumab Against Hydrogen Peroxide-Induced Oxidative Stress in Human RPE Cells

Abstract: CAPE has a protective effect on ARPE-19 cells against oxidative stress, and VEGF protein level and expression can be decreased by incubation with different concentrations of CAPE. These results demonstrate that CAPE suppresses the mitochondria-mediated apoptosis in ARPE-19 cells under oxidative stress. In addition, the use of CAPE in combination with bevacizumab has an additive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
3
12
0
1
Order By: Relevance
“…40,41 This phenomenon was normalized by N-acetylcysteine (NAC) ( Figure 1A). 40,41 This phenomenon was normalized by N-acetylcysteine (NAC) ( Figure 1A).…”
Section: Oxidative Stress Down-regulates Mir-205-5p Expressionmentioning
confidence: 98%
See 1 more Smart Citation
“…40,41 This phenomenon was normalized by N-acetylcysteine (NAC) ( Figure 1A). 40,41 This phenomenon was normalized by N-acetylcysteine (NAC) ( Figure 1A).…”
Section: Oxidative Stress Down-regulates Mir-205-5p Expressionmentioning
confidence: 98%
“…As previously observed, ARPE-19 cells resulted in a significant ROS production after 600 µM H 2 O 2 exposure. 40,41 This phenomenon was normalized by N-acetylcysteine (NAC) ( Figure 1A). Significantly reduced miR-205-5p levels were observed in ARPE-19 cells after H 2 O 2 exposure compared with control cells ( Figure 1B).…”
Section: Oxidative Stress Down-regulates Mir-205-5p Expressionmentioning
confidence: 98%
“…Genomic instability is generally compensated by DNA repair systems in a healthy individual. However, it has been reported that diminished antioxidant defense and DNA repair systems, which leads damaged genome and subsequent cell loss, contribute pathogenesis of many diseases (9,20,21). In the current study, alkali comet assay was used, which has been shown to be reliable, sensitive and cost effective method for detecting DNA strand breaks, alkali labile sites in DNA and incomplete excision repair sites at the level of a single cell.…”
Section: Resultsmentioning
confidence: 91%
“…Comparison of total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) values between the control and AMD groups Discussion RPE is exposed to excessive amounts of ROS due to chronic light exposure and high oxygen consumption. However, various antioxidant enzymes and defense mechanisms protect the RPE against oxidative damage (9,20,21). On the other hand, AMD has been suggested to be related with oxidative stress, as in many ocular diseases, whereas it is also wellknown that AMD is a multifactorial disease and underlying mechanisms are still unclear (1)(2)(3)(4)(5).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, they do not renew after differentiation ( Ebrahimi et al, 2017 ), inevitably resulting in RPE apoptosis caused by long-term oxidative damage. In severe AMD cases, these apoptotic RPE cells release VEGF, the most significant pro-angiogenic factor, resulting in the activation of CNV and the further development of wet AMD ( Dinc et al, 2017 ). Therefore, it is imperative to inhibit RPE cell apoptosis for abrogating subsequent angiogenesis in AMD.…”
Section: Introductionmentioning
confidence: 99%